Level of knowledge of peruvian physicians and dentists about the relationship between periodontal disease and systemic diseases. - Guerrero Moron, Jessica Estela (2024)
Introduction: The current scientific literature reflects a variability in the knowledge of dentists and physicians regarding the interactions between periodontal disease and systemic conditions. Objectives: To compare the level of knowledge about periodontal disease and its relationship with systemic alterations in dentists and physicians in the Peruvian army. Material y methods: A cross-sectional study was carried out on 188 participants (104 physicians and 84 dentists) selected by non-probabilistic sampling. The instrument consisted of two sections: a first part with the sociodemographic characteristics of the participants and a second part corresponding to the questionnaire to evaluate the level of knowledge. Results: When comparing the level of knowledge about periodontal disease and systemic alterations in dentists and physicians, no relationship was found between the level of knowledge and the profession at the general level (p = 0.208), by dimensions (p = 0.266 for diabetes mellitus, p = 0.195 for gestation and p = 0.09 for cardiovascular diseases), or according to sociodemographic data (p > 0.05). Conclusion: It was concluded that there is no difference between the level of knowledge of periodontal disease and systemic disorders in dentists and doctors of the Peruvian Army; furthermore, no significant associations were found between sociodemographic characteristics and the level of knowledge in dentists or physicians.